Quick Reference Guide for Plant Growth Regulators (PGR) in Florida Citrus Production - Tripti Vashisth; Jamie D. Burrow (EDIS, 2016)
This 2-page reference guide informs readers about PGRs, their use, and current research in Florida citrus. Written by Tripti Vashisth and Jamie D. Burrow, and published by the Horticultural Sciences Department, August 2016.